Evaluación de dos cepas (Cotopaxi y Tungurahua) de Rhizobium spp a dos dosis en el chocho (Lupinus mutabilis Sweet) VAR. INIAP - 450 (Andino), CEASA - Cotopaxi, 2021-2022 - Changoluisa Sangoquiza, Jesica Paola (2022)
This research project was carried out at Cotopaxi province, Eloy Alfaro Parish, Salache campus, at an altitude of 2,700 meters above sea level at Technical University of Cotopaxi. Agronomy Engineering career laboratory, a manual evaluation for conservation and multiplication of Rhizobium spp bacteria (Cotopaxi and Tungurahua) was carried out, inoculating in Lupinus to 2 solutions which are (1cc) and (2cc) submerging by seed at (Andino) variety, with the purpose to form nodules in the root (FBN), obtaining necessary doses, in field with an experimental design of complete random blocks DBCA was applied, with a factorial arrangement of 2x2+1 with three repetitions. ADEVA variance analysis was used to rank treatments and 5% Tukey test was applied for significant results. Acting the Rhizobium at initial phenological phase of Lupinus (chocho), the crop was obtained under controlled conditions, having an initial M.O. of 2.5%. Where germination results were obtained with 100% at 13 days between two strains, obtaining in first place D2 with a height of 38.31 at 66 days, also taking into account the number of leaves and flowered in a high range with Cotopaxi strain doses with (2cc). Where diameter and nodulation tend giving the first place to Tungurahua strain with doses (2cc). According to the number of nodules formed in two doses results in the strain (Tungurahua) dose (2cc) with a total number of 76 nodules in treatment TD2 keeping in the range (A) with a mean of 4.06 and the nodule size was between 0.4mm to 0.7mm, with Rhizobium controlled conditions of 25 to 30°C with a RH of 21%. The variety INIAP-450 (Andean) requires moderate dosage in the application of the bacteria when submerged.